Caerulomycin A suppresses the differentiation of naïve T cells and alleviates the symptoms of experimental autoimmune encephalomyelitis - Weshely Kujur; Rama Krishna Gurram; Sudeep K. Maurya; Sajid Nadeem; Sathi Babu Chodisetti; Nargis Khan; Javed Naim Agrewala (Taylor & Francis Group, 2017)
Multiple sclerosis (MS) is a highly detrimental autoimmune disease of the central nervous system. There is no cure for it but the treatment typically focuses on subsiding severity and recurrence of the disease. Experimental autoimmune encephalomyelitis (EAE) is an animal model of MS. It is characterized by frequent relapses due to the generation of memory T cells. Caerulomycin A (CaeA) is known to suppress the Th1 cells, Th2 cells, and Th17 cells. Interestingly, it enhances the generation of regulatory T cells (Tregs). Th1 cells and Th17 cells are known to aggravate EAE, whereas Tregs suppress the disease symptoms. Consequently, in the current study we evaluated the influence of CaeA on EAE. Intriguingly, we observed by whole body imaging that CaeA regressed the clinical symptoms of EAE. Further, there was reduction in the pool of Th1 cells, Th17 cells, and CD8 T cells. The mechanism involved in suppressing the EAE symptoms was due to the inhibition in the generation of effector and central memory T cells and induction of the expansion of Tregs. In essence, these findings implicate that CaeA may be considered as a potent future immunosuppressive drug.